Concentrated photovoltaic thermal (CPVT) solar collector systems: Part II - Implemented systems, performance assessment, and future directions - Sharaf, Omar Z. (2015)
Concentrated photovoltaic thermal (CPVT) solar collectors have been gaining ever-increasing attention from the scientific community and industrial developers due to their promising potential to pave the way for the penetration of solar energy into modern day power generation technologies. CPVTs׳ flexibility, manufacturability, high efficiency, and multi-output nature inspired many innovative designs and design improvements available in the literature. In this study, a comprehensive, up-to-date review of the governing scientific basics, system variations, and technological advances in CPVT systems will be presented. The study is split into two parts. The first part covers CPVTs’ characteristics and design considerations in addition to an overview of the principals and technological advances in the solar components that compose a CPVT (i.e., solar photovoltaics, solar thermal collectors, solar concentrator optics, and concentrated solar technologies). While the second part thoroughly covers CPVTs׳ published studies, application areas, performance assessment, commercial initiatives, and research prospects.